2017
DOI: 10.2494/photopolymer.30.271
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitivity Characteristics of Novel Resists Consisting of a Photobase Generator and an Epoxy Resin

Abstract: Most of the photopatterning materials based on epoxy resins are utilizing photoacid generators (PAGs) which generate superacids as catalysts. They have been used for high aspect ratio photoresists in the fabrication of MEMS devices. However, there is a drawback that the acidic species from PAGs will induce metal corrosion. One of the approach to overcome this problem is the use of photobase generators (PBGs) because organic bases would induce no corrosion. Although there is a large number of investigation of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In addition, Fukuda et al reported several types of o ‐hydroxy‐ trans ‐cinnamic acid‐derived PBG, which makes PSPI capable of developing in an aqueous alkali solution and resulting in an excellent pattern resolution 19,20 . Meanwhile, several new types of PBG have been investigated; for instance, Terada et al utilized an amine‐containing PBG to photocrosslink an epoxy resin‐bearing carboxylic acid group, resulting in a high pattern resolution with a film thickness of 10 μm 24 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Fukuda et al reported several types of o ‐hydroxy‐ trans ‐cinnamic acid‐derived PBG, which makes PSPI capable of developing in an aqueous alkali solution and resulting in an excellent pattern resolution 19,20 . Meanwhile, several new types of PBG have been investigated; for instance, Terada et al utilized an amine‐containing PBG to photocrosslink an epoxy resin‐bearing carboxylic acid group, resulting in a high pattern resolution with a film thickness of 10 μm 24 …”
Section: Introductionmentioning
confidence: 99%
“…19,20 Meanwhile, several new types of PBG have been investigated; for instance, Terada et al utilized an aminecontaining PBG to photocrosslink an epoxy resin-bearing carboxylic acid group, resulting in a high pattern resolution with a film thickness of 10 μm. 24 It is obvious to see that the reported PSPIs mostly focused on the development of photosensitive reagents and their combination with conventional thermally stable PI to formulate PSPI, but few studies have discussed the impact of chain rigid and film transparency on the performance of PSPI. For example, Zhu et al reported a series of studies on the structural design for PSPI-based liquid crystal alignment films.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, to improve the photosensitivity, we have designed a novel epoxy resin ( 4 ) bearing carboxylic acid groups to enhance cross‐linking reactions of epoxy groups (Scheme ) . It is expected that photogenerated amines would act as a catalyst in the reaction of epoxy groups and amines in the presence of a carboxylic acid as shown in Scheme .…”
Section: Introductionmentioning
confidence: 99%